Is rotating between static and dynamic work beneficial for our fatigue state?. (June 2016) - Luger, Tessy; Bosch, Tim; Hoozemans, Marco J.M.; Veeger, DirkJan H.E.J.; de Looze, Michiel P.
Abstract: Shoulder disorders comprise a large part of work-related musculoskeletal disorders. Risk factors, such as repetitiveness and monotony, may cause muscle fatigue and be attenuated by task rotation. We investigated rotation between a dynamic box-lifting task and a relatively static pick-and-place task and aimed to determine whether (1) a high rotation frequency leads to less fatigue development than a low rotation frequency, and (2) a self-selected rotation frequency leads to less fatigue development than imposed rotation frequencies. Ten participants performed four one-hour rotation schedules: two low frequency rotation schedules rotating at 30 min, one high frequency rotation schedule rotating every sixth minute, and a self-selected rotation schedule. Borg, SOFI and electromyography of Trapezius and Deltoid subparts served as fatigue indicators. We found significant signs of fatigue for most schedules regarding the Borg and SOFI ratings and the M. Trapezius pars Descendens. Task rotation frequency had no significant effect on any of the outcome parameters, whereas the self-selected rotation schedule clearly resulted in less development of perceived fatigue than imposed schedules. In conclusion, we think that freedom of rotation has the greatest potential to attenuate potential development of musculoskeletal disorders and we require due caution with the use and interpretation of EMG indicators of fatigue.